Minimally invasive spinal decompression for degenerative lumbar spondylolisthesis and stenosis maintains stability and may avoid the need for fusion. (April 2018) - Minamide, A.; Yoshida, M.; Simpson, A. K.; Nakagawa, Y.; Iwasaki, H.; Tsutsui, S.; Takami, M.; Hashizume, H.; Yukawa, Y.; Yamada, H.
Abstract : Aims: The aim of this study was to investigate the clinical and radiographic outcomes of microendoscopic laminotomy in patients with lumbar stenosis and concurrent degenerative spondylolisthesis (DS), and to determine the effect of this procedure on spinal stability. Patients and Methods: A total of 304 consecutive patients with single-level lumbar DS with concomitant stenosis underwent microendoscopic laminotomy without fusion between January 2004 and December 2010. Patients were divided into two groups, those with and without advanced DS based on the degree of spondylolisthesis and dynamic instability. A total of 242 patients met the inclusion criteria. There were 101 men and 141 women. Their mean age was 68.1 years (46 to 85). Outcome was assessed using the Japanese Orthopaedic Association and Roland Morris Disability Questionnaire scores, a visual analogue score for pain and the Short Form Health-36 score. The radiographic outcome was assessed by measuring the slip and the disc height. The clinical and radiographic parameters were evaluated at a mean follow-up of 4.6 years (3 to 7.5). Results: There were no significant differences in the preoperative measurements between the group and no significant differences between the clinical parameters at the final follow-up. The mean percentage slip was 17.1% preoperatively and 17.7% at the final follow-up (p = 0.35). Progressive instability was noted in 13 patients (8.2%) with DS and 6 patients (7.0%) with advanced DS, respectively (p = 0.81). There was radiological evidence of restabilization of the spine in 30 patients (35%) with preoperative instability. The success rate of microendoscopic laminotomy was good/excellent in 166 (69%), fair in 49 (20%) and poor in 27 patients (11%) in both groups. Conclusion: Microendoscopic laminotomy is an effective form of surgical treatment for patients with DS and stenosis. Preservation of the stabilizing structures using this technique prevents postoperative instability. Cite this article: Bone Joint J 2018;100-B:499–506.